Association between athletic participation and the risk of eating disorder and body dissatisfaction in college students - Blair, Laura; Aloia, Christopher R.; Valliant, Melinda W.; Knight, Kathy B.; Garner, John C.; Nahar, Vinayak K. (International Journal of Health Sciences, 2017)
Objective: Given that females exhibit a greater prevalence of eating disorders, there is of yet no conclusive evidence whether participation in college athletics exacerbates eating disorders or body shape dissatisfaction. This study assessed how gender and participation in collegiate athletics are associated with increased risk for disordered eating attitudes and body shape concerns in college students. Methods: This study used a cross-sectional research design. A total of 302 students at a Southern US university fully completed the eating attitudes test and the body shape questionnaire during class time or team meetings. Logistic regression was conducted to determine risk differentials for each group. Results: Of 302 students, 65.6% were females and 63.2% were non-athletes. Athletic status was significant as well but became slightly less so with adjustment (unadjusted at OR = 3.14, P < 0.001 vs. adjusted OR = 3.22, P < 0.001). Moreover, it was found that that non-athletic female students are slightly more at risk for disordered eating and significantly more dissatisfied with their body shape (OR = 5.95, P < 0.001). Conclusions: Although there seems to still be many unresolved issues regarding eating disorders, one thing is clear females are at higher risk, and it remains a significant challenge to college health services. College health practitioners should be made aware of the significant effect stress has on freshman in particular.